Роль изучения родного языка в становлении интеллектуального и духовного развития личности - Яяева, А.М. (Культура народов Причерноморья, 2013)
В статье рассматриваются вопросы роли изучения родного языка в становлении
интеллектуального и духовного развития личности на примере изучения крымскотатарского языка в
общеобразовательных учебных заведениях АРК. У статті розглядаються питання ролі вивчення рідної мови в становленні інтелектуального
і духовного розвитку особистості на прикладі вивчення кримськотатарської мови у загальноосвітніх
навчальних закладах АРК. The article deals with the native language and its role in personal intellectual and spiritual
development. It’s based on the research, done in Crimean Tatar secondary schools, located in the Crimean
Autonomous Republic. One of the directions of the humanization of education in Ukraine is the recognition of
personality – the highest value in society.
The native language or the language of ancestors as in itself can form individual’s worldview.
The history of the Crimean Tatar Public Education has deep roots in the distant past.
Due to the deportation of Crimean Tatar people in their place of exile, on May 18, 1944, the national education
in the Crimea was being destroyed.
In the 70 's – 80's, the Crimean Tatar language was being taught in exile, at several schools in Uzbekistan. It
was a small possibility for the Crimean Tatar pupils to study their native language. However, it was so
undertaken to restore national education system beyond the motherland.
In order to avoid the complete denationalization, the Crimean Tatar people have to learn their native language
as the way of communication. The important role in this process was given to the national school as the concept
of education.
Currently, the Autonomous Republic of Crimea counts only 15 Crimean Tatar secondary schools. Returning to
the genetic memory of the people, local ethnicities must begin to study their native language. It helps people to interpret the world. The young generation have to study the Crimean Tatar language’s literary standards,
listening, speaking and writing.